Legal Protection for Livestock Farmers in Core-Plasma Partnership Schemes: A Study of Unequal Contractual Relations - Azzah Salsabila, Fadhila (Jurnal Hukum In Concreto, 2024)
This study examines the legal dynamics of core-plasma partnerships in Indonesia, focusing on the structural imbalance between core companies and smallholder farmers. Although regulations such as Law No. 20 of 2008 and Ministry of Agriculture Regulation No. 13 of 2013 promote equitable collaboration, contractual practices often reflect asymmetry in bargaining power, particularly regarding pricing, exclusivity, and penalty clauses. Using a normative juridical method supported by statutory and case analysis, including KPPU Decision No. 09/KPPU-K/2020, the study reveals that legal protection for farmers remains largely formal and unenforceable due to weak regulatory oversight and limited access to justice. The findings highlight a gap between legal ideals and practical implementation, demonstrating how formal agreements may legitimize exploitative practices under the doctrine of contractual freedom. To address this, the study proposes legal reforms including independent contract review, standardized fair clauses, regulatory enforcement, and legal empowerment initiatives for farmers, aiming to realign partnership practices with principles of justice, accountability, and inclusive rural development.